Synthesis And Characterization Of Silver Nanoparticles For Antimicrobial Application In Natural Rubber Latex Foam By - Rathnayake, W. G. Indrajith Udayakantha (2014)
In this research project, natural rubber latex foam materials (NRLF) were developed with antimicrobial properties built-in within the natural rubber latex foam matrix by incorporating silver based nanomaterials using different techniques. The initial attempt was to optimize the chemical synthesis method of silver nanoparticles (SNPs) by varying the process parameters such as proportionate of reactant silver nitrate and tri-sodium citrate (TrSC), time of the reaction and the temperature conditions. It was found that, as the amount of TrSC was increased the obtained silver nanocolloid was more stable and consisted with mono-dispersed smaller sized SNPs. Next it was found that the incorporation of SNPs into the NRLF matrix can be accomplished via several techniques such as in-situ deposition of silver nanoparticles on NRLF (method 1), direct compounding method (method 2), using silver nanoparticles incorporated potassium oleate soap as both foaming and convenient carrier materials (method 3), green synthesis of silver nanoparticles inside natural rubber latex (method 4) and finally by incorporating silver doped titanium nanoparticles (Ag_doped TiO2) (method 5). It was found that the method 1 is the best method to incorporate smaller sized and consistently distributed SNPs into the natural rubber latex foam whereas the method 4 shows novel and easy way to incorporate SNPs into the NRLF. In addition, the last method showed the highest antimicrobial activities even though that method is difficult to carry out in large scale xxvii synthesis. It is observed that modified NRLF materials via all the five methods showed remarkable antimicrobial and anti-fungal properties against various kinds of pathogenic micro-organisms including Gram negative (G-) Escherichia coli (E.coli), Gram positive (G+) Staphylococcus aureus (SA), Staphylococcus epidermidis (SE) and Aspergillus niger (A. niger). Results obtained from the method 3, revealed the novel synthesis method of SNPs inside potassium oleate resulted soap material that can be directly used as an antimicrobial carboxylate soap. Results obtained from the method 4 confirmed that the novel green synthesis method of silver nanoparticles inside natural rubber latex can be easily carried out without using an additional stabilizing agent or a reducing agent. Furthermore it was found that the Ag doped TiO2 enhanced antimicrobial activities of NRLF by a great extent even in dark conditions.